A mai uráli nyelvészetről - Hajdú Péter (Acta Universitatis Szegediensis : sectio ethnographica et linguistica = néprajz és nyelvtudomány = étnografiâ i azykoznanie = Volkskunde und Sprachwissenschaft, 1965)
The present paper deals with current problems of Uralic linguistics in Hungary. Some aspects of recent investigations in this domain are disapproved of, e. g.: (1) taking too little interest in up-to-date theories of language; (2) predominance of diachronic and comparative methods in linguistic research; (3) hypertrophy of etymological comments and articles (NB. the author doesn't set a low value on etymology on the whole, but a great part of such topics seems to be, to a great extent, of secondary importance; (4) prevalence of mass-production and routine-work (the former appears often in bi- or multilingual publishing of the very same paper, too). Uralic lingustics in Hungary may overcome these difficulties by widening its theoretical background. By applying current trends in structural linguistics, a greater variety of principles, methods and themes could be obtained in this field: This implies, however, that one must give up the old-fashioned view, according to which the principal task of Uralistics is to develop only an extensive program in „pure" comparative linguistics.